Direct metal laser sintering process investigation: application to 3D slotted waveguide antennas. Issue 14 (14th September 2017) - Martin‐Guennou, Annaig; Quéré, Yves; Rius, Eric; Person, Christian; Enouz‐Vedrenne, Shaima; Lesueur, Guillaume; Merlet, Thomas
Abstract : Increasing demand for the development of multifunction radio‐frequency‐systems requires the fabrication of complex architectures. Three‐dimensional (3D) direct metal printing direct metal laser sintering (DMLS) has the required properties to build complex and robust parts. To determine whether this technology is able to replace traditional machining methods, it needs to be extensively examined. In the present study, several waveguides operating in a wide‐frequency range, and slotted waveguide antennas with relevant details and shape, operating in the Ku‐band, were designed, machined, assessed and measured. Measurements show that the degradation of component performances are related to the fabrication strategy used. Deterministic defects were observed that make it possible to conceive ways of enhancing manufactured parts. Through this analysis, the authors demonstrate the potential of the DMLS process to construct finely detailed complex and conformal structures.